Status and predictors of planning ability in adult long-term survivors of CNS tumors and other types of childhood cancer - Ernst, Mareike (Sci Rep, 2019)
Long-term childhood cancer survivors’ (CCS) quality of life can be impacted by late effects such as cognitive difficulties. Especially survivors of CNS tumors are assumed to be at risk, but reports of cognitive tests in CCS with survival times >25 years are scarce. We assessed planning ability, a capacity closely related to fluid intelligence, using the Tower of London. We compared 122 CNS tumor survivors, 829 survivors of other cancers (drawn from a register-based sample of adult long-term CCS), and 215 healthy controls (using sex-specific one-way ANOVAs and t-tests). Associations of CCS’ planning ability with medical and psychosocial factors were investigated with a hierarchical linear regression analysis. Mean planning ability did not differ between CCS and controls. However, female CNS tumor survivors performed worse than female survivors of other cancers and female controls. CNS tumor survivors of both sexes had a lower socioeconomic status, and fewer of them had achieved high education than other survivors. In the regression analysis, lower status and anxiety symptoms were associated with poor planning, suggesting possible mediators of effects of disease and treatment. The results indicate the necessity to contextualize test results, and to include cognitive and psychological assessments into aftercare.